(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate i) the different cover crops contribution used in no-tillage system (NT) to biogenic aggregation; and ii) the influence of aggregate formation pathways on the compartmentalization and the soil organic carbon origin. Two areas managed under NT with different implementation times (6 and 18 years, NT06 and NT18, respectively) and cover crops were evaluated, totaling six sampling areas: NT06, millet (NT06MI); NT06, brachiaria (NT06BR); NT06, sunn hemp (NT06SH); NT18, millet (NT18MI); NT18, brachiaria (NT18BR); NT18, and sunn hemp (NT18SH). In each sampling area, five pseudo-replicates were collected in the 0.00-0.05 and 0.05-0.10 m layers. The samples were air-dried and sieved using sieves with 9.7 and 8.0 mm mesh, and the aggregates retained within this interval were selected. The percentage of each type of aggregate (physicogenic and biogenic) was quantified. Total organic carbon (TOC) and the natural abundance of δ13C (‰) were analyzed and the physical fractionations of SOM were performed: particulate organic carbon (POC) and mineral-associated organic carbon (MAOC) and density fractionation (free light fraction carbon, FLFC). Physicogenic aggregates were quantified in greater proportion, except for the areas of NT06BR and NT18BR in the 0.00-0.05 m layer. The biogenic aggregates showed the highest contents of TOC, POC, MAOC, FLFC and more negative values of δ13C. The use of grasses, especially Brachiaria spp., as cover plants in NT after 6 and 18 years of adoption favors the formation of aggregates through the biogenic pathway and they influence the compartmentalization and origin of stored organic carbon.